IMPLEMENTASI AKUNTANSI SOSIAL DAN LINGKUNGAN DI INDONESIA - SUARYANA, AGUNG (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 1 (2011))
There has been a remarkable attention on social andenvironmental accounting recently. It informs us about social andenvironmental impact on operating activity of a company. Traditionalaccounting report only includes economic information for investors andcreditors’ interests. Social and environmental accounting has beendeveloped by various organizations in many countries. Accountingstandard in Indonesia has ruled it, however, there is a lack in theimplementation, especially in reporting prevention and maintenance ofenvironmental activities.To improve the implementation, there are several steps thatmust be done by the regulator. Firstly is to set standard ofsustainability reporting (SR) and mandate the implementation forcompanies doing environmentally related activities. Secondly, is tomandate companies to prepare SR in accordance to the existingguidelines, such as those issued by Global Reporting Initiative (GRI).Thirdly, is to award companies that have been implemented SR.Fourthly, is to conduct environmental audit to improve credibility of SR.Finally, is to develop GCG mechanism to protect the interests of allstakeholders.
Keywords: social and environmental accounting